Comparison of the responses of the yolk-sac fry of pike (Esox lucius) and roach (Rutilus rutilus) to low pH and aluminium: sodium influx, development and activity - Keinänen, Marja; Peuranen, Seppo; Nikinmaa, Mikko; Tigerstedt, Christina; Vuorinen, Pekka J. (Elsevier, 2000)
The responses of acidic water and aluminium on the newly-hatched yolk-sac fry of an acid-tolerant species, pike, and acid-sensitive species, roach were compared using 1–10-day exposures. Test solutions were made either in lake water (LW) with moderate ion content or in artificial water (AW) with low ion content ([Ca2 ] 0.12 and 0.034 mmol l 1, respectively). Roach fry died at pH 5.25 or below in the LW, being more sensitive in Al-containing water. There was a reduction in the exchangeable body Na concentration of roach concurrent with a reduction in the number of swimming fry in the Al concentration of 50 mg l 1 or higher at pHs 6.7, 5.75, and 5.25 in a 1-day test in the AW. Although pH down to 4.0 and Al concentrations up to 600 mg l 1 caused only partial mortality in pike during a 10-day exposure in LW, various sublethal effects augmented by Al were obvious. In addition to decreased swimming activity, the rates of ventilation, oxygen uptake, yolk absorption and growth as well as sodium influx (Jin Na) were reduced. The initial Jin Na in the control in roach was over three times higher than in pike. This difference may render roach more sensitive to low pH and Al. The Jin Na of roach was unable to recover from a 92% inhibition at pH 5.00 Al (200 mg l 1) in LW, whereas the Jin Na in pike recovered almost totally by day 9 at pH 4.00 without Al, and considerably at pH 4.75 Al (600 mg l 1) from 88 and 91% reductions, which in terms of molar fluxes were actually a quarter of the inhibition in roach. Both pike at pH 4.75 or 5.00 and roach at pH 5.75 in LW, if Al was not added, were able to increase the Jin Na and O2 uptake above the control levels (probably to compensate for the increased Na efflux). Although the percentage inhibition of Jin Na in a 1-day exposure to Al concentrations of 50, 100, and 200 mg l 1 at pH 5.0 in AW was similar in both species, the molar reduction of Jin Na was over three times higher in roach than in pike. High tolerance of pike yolk-sac fry to acidic Al-containing water is concluded to be interrelated to a low ion exchange rate as compared to acid-sensitive roach. The reduction in metabolism in Al-containing water further reduces ion loss and might provide even longer survival of pike yolk-sac fry.
Keywords: acidic water; yolk-sac fry; sodium influx; hauki; särki; acidity; aluminium; Esox lucius; Rutilus rutilus; yolk sac; oxygen consumption